Towards experimental and numerical assessment of the vibrational serviceability comfort of adhesive free laminated timber beams and CLT panels assembled using compressed wood dowels. (1st August 2020) - Bui, T.A.; Oudjene, M.; Lardeur, P.; Khelifa, M.; Rogaume, Y.
Highlights: Adhesive free engineered timber beams and CLT panels have been manufactured. Multi-layer timber beams and CLT panels assembled using compressed wood dowels have been experimentally tested. Vibrational serviceability comfort of CLT panels assembled using compressed wood dowels has been assessed. A 3D FE model has been developed and validated experimentally for vibrational behaviour. Vibrational serviceability performance of a large-scale CLT panel has been predicted numerically and compared to the Eurocode 5 design requirements. Variability of the experimental results has been studied. Abstract: This paper presents experimental and numerical investigations on the vibrational serviceability performance of novel adhesive free engineered wood products (AFEWPs), namely adhesive free laminated timber beams (AFLB) and adhesive free cross-laminated timber panels (AFCLT), assembled through thermo-mechanically compressed wood dowels (CWD). The laminations composing the AFEWPs are made of oak timber while the CWD are made of spruce. The experimental modal analyses were carried out under free-free conditions using a hammer impact. Natural frequencies, mode shapes, and damping ratios were assessed experimentally. In addition, similar glued beams made of oak timber (conventional glulam) were manufactured and tested for comparison purpose. A predictive 3D FE model was developed and validated by comparison against experimental data and then used to predict the vibrational behavior of a realistic flooring system made with AFCLT panel and measuring 4.5 m × 5.5 m. The predicted FE results were discussed with regard to the Eurocode 5 vibrational serviceability design requirements showing acceptable vibrational performance. The variability level of the results for the AFEWPs is also studied and discussed.